Corynebacterium freneyi as a cause of early prosthetic valve endocarditis. Issue 11 (11th November 2021) - Grenne, Bjørnar; Dalen, Håvard; Nordhaug, Dag Ole; Sand-Aas, Torgeir; Holte, Espen; Damås, Jan Kristian; Mjølstad, Ole Christian
Abstract : Infective endocarditis (IE) is associated with severe complications and a high mortality rate. Identification of the causative pathogen is crucial to optimise treatment. We present a case of prosthetic valve endocarditis caused by Corynebacterium freneyi, a very rare cause of human infection and not previously reported as a cause of IE. Despite proper antibiotic therapy, the patient eventually needed surgery after progression of the infection. After surgery, he quickly recovered without evidence of relapse during an 8-month follow-up period. This report highlights critical decision making in a complex and potentially life-threatening situation, where neither guidelines nor previous clinical or microbiological experience were able to give clear treatment recommendations.